ANALISIS QSAR SENYAWA TURUNAN DIOSMETIN SEBAGAI ANTIOKSIDAN BARU DENGAN METODE SEMI EMPIRIK AM 1 - Mulatsari, Esti; Martati, Titiek; Mumpuni, Esti; Hidayat, Andika Muhammad (Jurnal Farmasi Indonesia, 2019)
Diosmetin is a bioflavonoid that abundant in nature and it is flavone derived compound that have low antioxidant activity so the utilization of diosmetin as an antioxidant is very rare. To optimize the utilization of diosmetin as an antioxidant, diosmetin chemical structure was developed using QSAR methode. Quantitative Structure and Activity Relationship (QSAR) analysis of 195 diosmetin derived compound have been performed using electronic descriptors i.e heat formation, HOMO energy, LUMO energy, Log P value, mass, C2, C4, and C4?. The electronic structure as descriptor were analyzed using Hyperchem 8.0.6 software for Windows 7.0 using AM1 semi-empirical method. The descriptors were obtained by molecular modelling to obtain the most stabile structure after geometry optimation process. The best QSAR equation model was determined by multilinier regression approach. The best QSAR equation is ?log IC50 = 70.52781 + (-0.0298 Panas Pembentukan) + (3.627483 Energi HOMO) + (-0.48695 Energi LUMO) + (0.274203 Energi Hidrasi) + (-3.43515 Log P) + (-0.17476 Massa) + (26.95107 muatan atom C2) + (-3.67587 muatan atom C4) + (-3.85701 muatan atom C4?). The result of the IC50 prediction value showed that 3,6-diamin diosmetin is a diosmetin derived compound that have the best antioxidant activity with IC50 value 0.33 µg/mL.